Naturally occurring influenza reassortment in pigs facilitates the emergence of intrahost virus subpopulations with distinct genotypes and replicative fitness - Chong Li; Victoria Meliopoulos; Aaron Rendahl; Stacey Schultz-Cherry; Montserrat Torremorell (mBio)
ABSTRACT Pigs are recognized as amplifying hosts for influenza A virus (IAV) reassortant viruses. Understanding the extent of IAV reassortment occurring at the individual pig level in naturally infected pigs and how reassortment impacts virus diversity, persistence, and replicative fitness is essential for countering IAV threats to humans and animals. Here, 244 IAV plaques were isolated from 24 commercial pigs, resulting in 26 distinct genome segment constellations. About 33% (8/24) of pigs were infected with two or more different genotypes, with two pigs harboring two or more different subtypes. Our results indicate that few pigs in a population harbor significantly more genotypes than other pigs and generate most of the diversity, including the emergence of reassortants. However, detecting distinct genotypes during surveillance was dynamic, with most of the genotypes subsiding over time. All the IAV genotypes could replicate in various swine and human-sourced respiratory epithelial cells, and we observed that distinct reassortant genotypes recovered from a single pig could exhibit different growth abilities, especially in human cells. Overall, we demonstrated that multiple distinct IAV genotypes with distinct antigenic profiles and varying growth abilities on swine and human respiratory tracts can be shed simultaneously from a single pig, which contributes to the dynamic nature of IAV prevalence. The striking magnitude of IAV reassortment at the single pig level revealed in this study highlights the need to strengthen surveillance efforts and plans to eliminate IAV from swine farms because pigs have a high potential to produce diverse and potentially zoonotic influenza reassortant viruses.IMPORTANCEPigs play a crucial role in driving influenza A virus (IAV) diversification and evolution by reassorting the viruses originating from different hosts. Despite IAV reassortment and diversity being well documented in pig populations at different scales (e.g., farm, region, country), limited field research has explored the extent of reassortment happening at the single pig level and how that contributes to the overall genetic and biological variation observed in populations. We provide initial information on levels of reassortment happening at the single pig level in naturally infected pigs, and that particular pigs can shed a plethora of distinct genotypes, with certain genotypes having distinct replicative fitness on swine and human respiratory tracts, which preserves the potential for IAV long-term evolution and facilitates the emergence of zoonotic/pandemic-capable reassortants.